Economy, psychology and stock investment: analysis of variables that participate in the process of decision making (2012)
The ININBE questionnaire has been recently validated in order to measure the variables that affect individual investor behavior in stock exchange. The lack of information about the methodology, items selection and psychometric properties of the instruments used in other researches has shown the necessary to elaborate and validate a questionnaire. In the present work we have applied the ININBE questionnaire to 257 individual investors. We have found interesting results about the relationship between the “psychological” and “economical” variables with individual investor’s characteristics.